2021
DOI: 10.1371/journal.pmed.1003779
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural activation to prevent depression and loneliness among socially isolated older people with long-term conditions: The BASIL COVID-19 pilot randomised controlled trial

Abstract: Background Older adults, including those with long-term conditions (LTCs), are vulnerable to social isolation. They are likely to have become more socially isolated during the Coronavirus Disease 2019 (COVID-19) pandemic, often due to advice to “shield” to protect them from infection. This places them at particular risk of depression and loneliness. There is a need for brief scalable psychosocial interventions to mitigate the psychological impacts of social isolation. Behavioural activation (BA) is a credible … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 45 publications
1
52
0
3
Order By: Relevance
“…Nine interviews were carried out with the BASIL Support Workers who delivered the intervention (characteristics reported elsewhere 12 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine interviews were carried out with the BASIL Support Workers who delivered the intervention (characteristics reported elsewhere 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Completer participants had between 2-8 of a maximum 8 intervention sessions (mean = 6.5). Participant demographics for the pilot trial are reported elsewhere 12 along with a summary of the thematic analysis (see also Appendix 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In time we anticipate that the results of BASIL + will contribute to Cochrane reviews in this topic [54]. BASIL + builds on the work conducted in the BASIL-C19 external pilot RCT [23] and will provide further lessons for the efficient delivery of mental health trials beyond the pandemic. The current work will be important in contributing to the emerging knowledge that trials can be conducted more efficiently and resourcefully when networks and research communities come together to work collaboratively with a united goal.…”
Section: Discussionmentioning
confidence: 99%
“…Costs of intervention and health service use will be calculated using a bottom-up costing approach. Resources used to deliver the intervention will be obtained from the study team, whereas health and social service resource use will be measured using a brief, tailored resource-use questionnaire, developed based on the questionnaire used in the BASIL C-19 pilot study [23]. Unit costs of health and social service use will be obtained from the UK national reference costs [47] and the Unit Costs of Health and Social Care report [48].…”
Section: Methodsmentioning
confidence: 99%